Massive rectorrhage due to pulmonary and intestinal tuberculosis: A case report - Jose Luis Estela-Zape; Leonardo Arzayus Patiño; Valeria Sanclemente-Cardoza (IDCases)
Tuberculosis is a bacterial infection that predominantly affects the lungs, although it can also affect other organs, including the intestine. Massive rectal bleeding, characterized by severe rectal bleeding, is a rare but serious complication of intestinal tuberculosis, with an estimated incidence of 5 % of tuberculosis patients. This report describes the case of a 21-year-old woman with active tuberculosis and comorbidities such as asthma and a history of psychoactive substance use, who developed massive rectal bleeding and significant clinical deterioration, manifested by excessive bleeding and septic shock, which resulted in fatal outcome.